Crowdfunding: a new normal in Malaysia / Anita Abu Hassan, Fauziah Mohamad Yunus and Mohd Syazrul Hafizi Husin - Abu Hassan, Anita; Mohamad Yunus, Fauziah; Husin, Mohd Syazrul Hafizi (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Rapid development in information technology and the emerging of the digital world have shifted ways of doing things. More and more industries have moved away from the traditional business operations to new operations environments using digital technology with the help of the internet or network connection. In financing industries, capital markets and financial institutions would be the best financing sources to finance businesses. Capital market is specifically designed to finance public listed companies whereas the financial institution focuses on the businesses which do not have the access to the capital market. The financial institution is very selective in providing financing to its borrower due to several risk factors such as repayment risk, industry risk, and collateral issues, just to name a few.